High Mortality of Huisache (Vachellia farnesiana) with Extreme Fire During Drought - Victoria M. Donovan; Allie V. Schiltmeyer; Carissa L. Wonkka; Jacob Wagner; Devan A. McGranahan; William E. Rogers; Urs P. Kreuter; Dirac Twidwell (Fire, 2025)
The almost complete eradication of fire from grasslands in North America has led to non-linear hysteretic transitions to shrub- and woodlands that the reintroduction of low-intensity fire is unable to reverse. We explore the ability of the extreme ends of variation in fire behavior to help overcome hysteretic threshold behaviors in huisache (Vachellia farnesiana) encroached grasslands. We contrasted experimental fire treatments with unburned control areas to assess the ability of extreme fires burned during drought to alter the density and structure of huisache. We found that extreme fires reduced the density of huisache by over 30% compared to control plots, both through driving huisache mortality and reducing the number of new recruits following treatments. For instance, extreme fire drove 48% huisache mortality compared to 4% in control treatments. For surviving plants, the number of stems increased but the crown area did not significantly change. Prescribed fire, conducted under the right conditions, can drive high mortality in one of the most notorious encroaching species in the southern U.S. Great Plains. With the fire conditions observed in this study likely to increase under future climate projections, utilizing extreme fire as a management tool for huisache will help scale up management to meet the growing extent of woody encroachment into grasslands.